Cooperative mixing through hydrodynamic interactions in Stylonychia lemnae - Régis Turuban; Giovanni Noselli; Alfred Beran; Antonio DeSimone (Proceedings of the National Academy of Sciences, 2025)
Aquatic microorganisms typically inhabit a heterogeneous resource landscape, composed of localized and transient patches. To effectively exploit these resources, they have evolved a wide range of feeding strategies that combine chemotactic motility with active feeding flows. However, there is a notable lack of experimental studies that examine how these active flows shape resource fields to optimize feeding. In particular, the suspected cooperative hydrodynamics provided by groups of cells remains largely unexplored due to the difficulties in visualizing these dynamic three-dimensional flows. Here, we experimentally investigate how Stylonychia lemnae ciliates form feeding clusters of independent cells around food patches. Individual feeding flows interact hydrodynamically to create a chaotic collective flow at the population scale. Using a combination of experimental and numerical techniques, we measure and predict the entire collective flow, enabling us to assess its remarkable mixing and dispersion properties. We show that the active spreading of the food patch accelerates its detection by starving cells. As many fitness advantages provided by collective flows can be envisioned, we propose that this feeding cluster represents a form of intraspecific by-product cooperative behavior.